Auditor's Ability to Detect Fraud: Analysis of Internal and External Factors - Agung, Raden Aji Pangersa; Widyasari, Widyasari (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the influence of internal and external factors on auditors’ ability to detect fraud. The internal factors examined include experience and professional skepticism, while the external factors consist of workload and time pressure. The subjects of this study were auditors working at the Audit Board of the Republic of Indonesia (BPK RI). The sample was selected using a purposive sampling method, with valid responses obtained from 109 auditors. Data were collected through an online questionnaire and analyzed using SPSS version 26.0 and Microsoft Excel 2021. The analysis method used was multiple linear regression, along with classical assumption testing and instrument validity and reliability tests. The results show that experience and professional skepticism have a positive and significant effect on auditors’ ability to detect fraud. In contrast, workload and time pressure do not have a significant effect. These findings highlight the importance of strengthening internal auditor factors—particularly through enhancing experience and fostering professional skepticism—to support the effectiveness of fraud detection in the audit process.